Pakistani Undergraduate Students’ Perceptions of Ecocriticism in Relation to Two Novels: A Case Study of a Public-sector College District Vehari - Ghulam Yasin; Ghazal Shaikh (University of Chitral Journal of Linguistics and Literature, 2024)
The research study aims to explore undergraduate students' perceptions of ecocriticism in relation to two selected novels at a public-sector postgraduate college in Vehari, Pakistan. The selected novels are The God of Small Things by Arundhati Roy (1997) and Things Fall Apart by Chinua Achebe (1958). The study relies upon the single research question: ‘How does the sample of undergraduate students in Vehari college perceive ecocriticism in fiction?’ The framework of ecocriticism by Glotfelty (1996) was utilized guiding the research work. Semi-structured interviews were conducted for collecting research data by eight participants doing their BS English in the same college. The study is distinctive because it explores the participants’ perceptions of ecocritical themes in fictions and also connects their social and personal experiences with the themes portrayed in the selected novels. The findings reveal that the participants discussed and connected ecocriticism and its themes in the novels that were contextually and culturally closer to their experiences. The findings of the study are important for teachers and researchers working in the field of ecocriticism and fiction because they present considerable insights into the students’ perceptions of ecocriticism related to the study of novels.